Impact of governance and globalization on natural resources volatility: The role of financial development in the Middle East North Africa countries. (September 2022) - Liu, Haiying; Saleem, Muhammad Mansoor; Al-Faryan, Mamdouh Abdulaziz Saleh; Khan, Irfan; Zafar, Muhammad Wasif
Abstract: Developing countries have experienced persistent increases in population growth and surging supply-demand gaps in natural resources. The growing resource gap has exposed fragile economies to a volatile environment when prices move rapidly upward. This study attempts to assess the role of macroeconomic policy indicators in determining the frequent and rapid price changes of natural resources by using data from 1996 to 2020. Neo-Classic growth theories have considered prices of natural resources as an exogenous factor affecting various macroeconomic variables; however, this study attempts to explore the long-run impact of governance and globalization on natural resource prices and acknowledge it as an endogenous factor. Second-generation methods have been used to assess heterogeneity and unit root in this study. Westerlund and Edgerton co-integration test results show the presence of co-integration among the study variables. This study has empirically estimated long-run elasticities and maintained the positive impact of globalization and governance on the volatility of natural resource prices for the Middle East North Africa countries. However, financial development and income reduce natural resource price volatility in these countries. This study also suggests policy implications based on empirical analysis. Highlights: Impact of governance and globalization on natural resources volatility checked. Second-generation Cup-FM and Cup-BC are employed for empirical analysis. Globalization significantly contributes to exacerbating natural resource prices. Quality of governance has a positive impact on natural resource price volatility. Financial development reduces natural resource price volatility.